2014
DOI: 10.1038/cdd.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as divine messengers: are they the Hermes of modern molecular oncology?

Abstract: Exosomes are cell-derived vesicles that convey key elements with the potential to modulate intercellular communication. They are known to be secreted from all types of cells, and are crucial messengers that can regulate cellular processes by 'trafficking' molecules from cells of one tissue to another. The exosomal content has been shown to be broad, composed of different types of cytokines, growth factors, proteins, or nucleic acids. Besides messenger RNA (mRNA) they can also contain noncoding transcripts such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
197
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(203 citation statements)
references
References 110 publications
(147 reference statements)
0
197
0
1
Order By: Relevance
“…Therefore, enriched vesicles having similar morphology and size consistent with exosomes are defined as exosome-like vesicles . Exosomes can facilitate intercellular communication by transferring proteins and non-coding RNAs (such as microRNAs; miRNAs) (Kahlert and Kalluri, 2013;Braicu et al, 2014). Although some functions or mechanisms remain elusive, it has been demonstrated that exosomes can modulate their neighboring cells by influencing major cellular process including apoptosis, cell differentiation, proliferation and metabolism (Qin et al, 2016;Braicu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, enriched vesicles having similar morphology and size consistent with exosomes are defined as exosome-like vesicles . Exosomes can facilitate intercellular communication by transferring proteins and non-coding RNAs (such as microRNAs; miRNAs) (Kahlert and Kalluri, 2013;Braicu et al, 2014). Although some functions or mechanisms remain elusive, it has been demonstrated that exosomes can modulate their neighboring cells by influencing major cellular process including apoptosis, cell differentiation, proliferation and metabolism (Qin et al, 2016;Braicu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes can facilitate intercellular communication by transferring proteins and non-coding RNAs (such as microRNAs; miRNAs) (Kahlert and Kalluri, 2013;Braicu et al, 2014). Although some functions or mechanisms remain elusive, it has been demonstrated that exosomes can modulate their neighboring cells by influencing major cellular process including apoptosis, cell differentiation, proliferation and metabolism (Qin et al, 2016;Braicu et al, 2014). One obvious point about the content of exosomes is that they contain miRNAs, which can inhibit translation of mRNAs by targeting 3′ untranslated regions (UTRs) (Batiz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…gastric cancer (GC) cells and pancreatic cancer cells). 6 Exosomes contain various proteins, messenger RNA (mRNA), and microRNA (miRNA), depending on…”
Section: Introductionmentioning
confidence: 99%
“…61 Our results implied that increased KRT5 expression in cells might be required for cellular function, but not for transfer to recipient cells. Figure 6D shows the signal intensification of protein biomarkers in exosomes compared to their parent cells (ratio of exosomal/cellular fold changes from the data shown in Figures 4B and 6C).…”
Section: Kim Et Almentioning
confidence: 69%